Development, implementation, and scalability of the Family Engagement in Research Course: a novel online course for family partners and researchers in neurodevelopmental disability and child health - Cross, Andrea; Soper, Alice Kelen; Thomson, Donna; Putterman, Connie; McCauley, Dayle; Micsinszki, Samantha; Martens, Rachel; Solomon, Patricia; Carter, Lorraine; Reynolds, James N; Kraus de Camargo, Olaf; Gorter, Jan Willem (Research Involvement and Engagement, 2024)
Background Since 2011 when the Canadian Institutes of Health Research launched the Strategy for Patient Oriented Research, there has been a growing expectation to embed patient-oriented research (POR) in the health research community in Canada. To meet this expectation and build capacity for POR in the field of neurodevelopmental disability and child health, in 2017 researchers and family leaders at CanChild Centre for Childhood Disability Research, McMaster University partnered with Kids Brain Health Network and McMaster Continuing Education to develop and implement a 10-week online Family Engagement in Research (FER) Course. Main text From its inception, the FER Course has been delivered in partnership with family leaders and researchers. The FER Course is innovative in its co-learning and community building approach. The course is designed to bring family partners and researchers together to co-learn and connect, and to develop competency and confidence in both the theory and practice of family engagement in research. Coursework involves four live online group discussions, individual review of course materials, weekly group activities, and a final group project and presentation. Upon completion of the FER Course, graduates earn a McMaster University micro-credential. Conclusions To meet a need in building capacity in POR, a novel course in the field of neurodevelopmental disability and child health has been co-created and delivered. Over six years (2018–2023), the FER Course has trained more than 430 researchers and family partners across 20 countries. A unique outcome of the FER Course is that graduates expressed the wish to stay connected and continue to collaborate well beyond the course in turn creating an international FER Community Network that continues to evolve based on need. The FER Course is creating a growing international community of researchers, trainees, self-advocates, and family partners who are championing the implementation of meaningful engagement in neurodevelopmental disability and child health research and beyond. The course is internationally recognized with an established record of building capacity in POR. Its uptake, sustainability, and scalability to date has illustrated that training programs like the FER Course are necessary for building capacity and leadership in family engagement in research.
Keywords: family engagement in research; child health; neurodevelopment disability; patient-oriented research; online education